STATE FINANCE AND ECONOMIC GROWTH: UNDERSTANDING CERTAIN DISPARITIES AND IMBALANCES - Chauhan, Pitamber Singh (International Journal of Research -GRANTHAALAYAH, 2024)
The significant decline in state finances over the past decade, marked by sharp increases in revenue, fiscal and primary deficits, rising debt levels, contingent liabilities, and cuts in capital and maintenance spending, has raised considerable concerns among policymakers. The limited growth of central transfers and the impact of central pay revisions have been particularly damaging to state finances. Additionally, the states' own fiscal performance has worsened considerably. Regarding the transfer system, the Ministry of Finance's proposed scheme aims to tie part of the transfers to fiscal reforms. However, the design of the scheme presents serious issues, and its effectiveness remains uncertain. The paper outlines the key areas of reform that states should prioritize to enhance efficiency, boost revenue generation, and focus on reducing unproductive expenditures.